Peningkatan Hasil Belajar IPS Peserta Didik Tentang Perbedaan Iklim Melalui Model Pembelajaran Kooperatif Tipe Gallery Walk di Kelas IV SDN 015/X Kuala Lagan Semester Ganjil Tahun Ajaran 2021/2022 - Ramli Ramli (Departement of Mathematics Education, 2022)
This study aims to describe and obtain information on improving social studies learning outcomes through the Gallery Walk type cooperative learning model. This research is classroom action research consisting of two cycles, each cycle consisting of two meetings. Each meeting consists of four stages, namely planning, implementation, observation, and reflection. The subjects of this study were fourth grade students at SDN 015/X Kuala Lagan, totaling 14 people. This research was conducted in the odd semester of the 2021/2022 academic year. Data collection techniques using tests, observations, and documentation. Data were analyzed using percentages and data reduction. The results showed that the Gallery Walk learning model could improve social studies learning outcomes for fourth grade students at SDN 015/X Kuala Lagan by giving praise.